Relation between dimensional distinctiveness and comparison format in a novel noun generalization task in preschoolers - Lagarrigue, Yannick; Thibaut, Jean-Pierre (Frontiers in Psychology, 2025)
Numerous studies have shown that in novel noun generalization tasks, the simultaneous presentation of multiple learning examples increases the percentage of generalizations that are based on a priori less salient properties, compared to the presentation of a single learning example. In this research with preschoolers (n = 300) we demonstrate that this effect can be modulated by dimensional distinctiveness, i.e., how easy it is to determine whether two dimension values (shape and 2D texture) are easy to distinguish or not. In a first experiment, we manipulate dimensional distinctiveness globally (both shape and 2D texture are distinctive, or not) and explore how it interacts with comparisons format: two learning examples from the same category (i.e., within-category comparison), two learning examples from different categories (i.e., between-category comparison), and no-comparison (i.e., only one learning example). Results show that within-category comparisons yielded more taxonomic generalizations than between-category comparisons and no-comparison conditions. Furthermore, children selected more often the taxonomic match with highly distinctive stimuli than with low distinctive stimuli. In a second experiment, we independently manipulate the distinctiveness of stimuli shape and 2D texture to determine which dimension distinctiveness might contribute to better generalization in a within-comparison format. Results indicated that within-category comparisons resulted in more taxonomic generalization with distinctive textures, regardless of shape distinctiveness. These findings suggest that not all comparison conditions are equals and that children’s generalizations may be influenced by the characteristics of the stimuli.